Histórias, poderes, disputas e resistências: trabalhadores em uma Junta de Conciliação e Julgamento (Itacoatiara, AM, 1979-1984) - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
The present research sought to investigate the different life experiences, perspectives of resistance and practices of organization of workers in disputes for rights in the city of Itacoatiara, from the analysis of the labor processes of the Board of Conciliation and Judgment of Itacoatiara (JCJ-ITA ). For these analyzes, we started from documentation filed and preserved by the Labor Justice Memory Center of the 11th Region (CEMEJ/TRT11), where the individual disputes from 1979 to 1984 are found. From this periodization, we intend to revalue the experiences of those subjects and understand their struggles and social practices in that period of civil-military dictatorship (1964/1985). The empirical observation of these relationships, through a series of reading of labor processes, led us to analyze the culture of rights built by the group of male and female workers, so that their speeches and political positions show meanings constructed and attributed regarding their life rights, work, rest, health, leisure, among other dimensions that make up their lives, highlighting perspectives on the past and other projects for the future and present.
Keywords: Disputas por direitos; Itacoatiara (AM); Junta de Conciliação e Julgamento de Itacoatiara; Dissídios individuais; Posicionamento político; CIÊNCIAS HUMANAS; Trabalhadores; Processos trabalhistas; Ditadura civil-militar; Itacoatiara